Evaluation of transport-related outcomes for neonatal transport teams with and without physicians. Issue 7 (27th May 2021) - Abdelmawla, Mohamed; Hansen, Gregory; Narvey, Michael; Whyte, Hilary; Ilodigwe, Don; Lee, Kyong-Soon
Abstract: Objective: The aim of this study was to evaluate if the presence of a physician in the neonatal transport team (NTT) affects transport-related outcomes and procedural success. Design: Retrospective cohort study with propensity score matching. Setting: Canadian national study. Patients: Neonatal transports from nontertiary centres between January 2014 and December 2017. Interventions: Comparison of transports conducted by NTTs with physicians (MD Group) and without physicians (noMD Group). Main outcome measures: The primary outcome was the change in patient acuity as measured by the transport risk index of physiologic severity (TRIPS) score. Secondary outcomes included mortality within 24 hours of NICU admission, clinical complications during transport, procedural success, and stabilization time. Results: Among 9, 703 eligible cases, 899 neonatal transports attended by NTTs with physicians were compared to 899 neonatal transports without physicians using propensity score matching. No differences were seen in the improvement of TRIPS score or mortality ≤24 hours of NICU admission. The MD Group had more clinical complications (7.7% versus 5.0%, P=0.02). No differences were seen in success rates of invasive procedures. The MD Group had shorter stabilization times. In multivariable analysis, the MD Group was not a significant predictor for the improvement in TRIPS score after adjustment for covariates. Conclusions: Neonatal transports conducted by teams including physicians compared to teams without physicians, did not have higher improvement in TRIPS scores and had similar success rates for procedures. These results provide insights for the planning of the structure and training of specialized interfacility neonatal transport programs.